2007
DOI: 10.1002/art.23061
|View full text |Cite
|
Sign up to set email alerts
|

Role of hypoxia and cAMP in the transdifferentiation of human fetal cardiac fibroblasts: Implications for progression to scarring in autoimmune‐associated congenital heart block

Abstract: Objective. Identification of isolated congenital heart block (CHB) predicts, with near certainty, the presence of maternal anti-SSA/Ro antibodies; however, the 2% incidence of CHB in first offspring of anti-SSA/ Ro؉ mothers, 20% recurrence in subsequent pregnancies, and discordance in identical twins suggest that an environmental factor amplifies the effect of the antibody. Accordingly, this study was carried out to explore the hypothesis that hypoxia potentiates a profibrosing phenotype of the fetal cardiac f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 40 publications
0
22
2
1
Order By: Relevance
“…Hypoxia is known to induce differentiation from fibroblasts to myofibroblasts (6). However, mRNA levels of myofibroblast markers, such as TGF-β1, p21, and α-SMA, were not increased in our hypoxia-exposed cells.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Hypoxia is known to induce differentiation from fibroblasts to myofibroblasts (6). However, mRNA levels of myofibroblast markers, such as TGF-β1, p21, and α-SMA, were not increased in our hypoxia-exposed cells.…”
Section: Discussioncontrasting
confidence: 64%
“…Therefore, we next examined the mRNA expression levels of TRPM2 channels and KCa3.1 in cardiac fibroblasts exposed to hypoxia and normoxia. In addition, we also examined the expression levels of marker mRNAs for myofibroblasts, for example, transforming growth factor (TGF)-β1 (24), cyclin-dependent kinase inhibitor 1 (p21), and α-smooth muscle actin (α-SMA) (25), because hypoxia is known to induce differentiation from fibroblasts to myofibroblasts (6). As illustrated in Fig.…”
Section: Effect Of Hypoxia On Trpm2 Mrna Expression In Rat Cardiac Fimentioning
confidence: 99%
See 1 more Smart Citation
“…It can therefore be speculated that the relative state of chronic hypoxia in which the human heart develops is necessary for the normal development of the cardiovascular system (Webster & Abela, 2007). Clancy et al (2007) showed that hypoxia is thought to contribute to differentiation of human fetal cardiac fibroblasts into myofibroblasts in vitro (Clancy et al, 2007). It has also been postulated that fetal death in ICP may be mediated by bile acid induced vasoconstriction of placental vessels leading to acute hypoxia in these fetuses (Mays, 2010;Sepúlveda et al, 1991).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The effect of hypoxia on fibroblasts is attenuated by UDCA A fetus develops in a state of partial hypoxia during pregnancy (Clancy et al, 2007;Patterson and Zhang, 2010;Webster and Abela, 2007). Therefore, further investigation into the effect of hypoxia on neonatal rat and human fetal fibroblasts was carried out.…”
Section: 7mentioning
confidence: 99%